Light, daylighting and fluctuation of illuminance level in office buildings - Elina Mohd Husini; Fadli Arabi; Wan Norisma Wan Ismail; Raja Md Yazit R.N.S.; Jaafar N.H. (Institute of Physics Publishing, 2024)
Indexed by Scopus